1986
DOI: 10.1055/s-0038-1661561
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies Against Human High Molecular Weight Urinary Urokinase: Application for Affinity Purification of Urinary Prourokinase

Abstract: SummaryMonoclonal antibodies against urinary urokinase were obtained by immunizing mice with purified human high molecular weight urokinase. Five antibodies were selected and denominated MPW1UK, MPW2UK, MPW3UK, MPW4UK, and MPW5UK, respectively. All selected antibodies reacted with high and low molecular weight urokinase. Cleavage of the low molecular weight paranitroanilide substrate pyro-Glu-Gly-Arg-pNA by urokinase was not inhibited by the antibodies and only one antibody (MPW5UK) inhibited plasminogen activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…1 mg human plasmin was coupled to 1 ml CNBr activated Sepharose to obtain plasmin Sepharose (26). Monoclonal antibodies against u-PA were produced and charac terized as described previously (27). MPW 5 U K was finally selected and peroxidase labelled according to the method of Nakane and Kawaoi (28).…”
Section: Methodsmentioning
confidence: 99%
“…1 mg human plasmin was coupled to 1 ml CNBr activated Sepharose to obtain plasmin Sepharose (26). Monoclonal antibodies against u-PA were produced and charac terized as described previously (27). MPW 5 U K was finally selected and peroxidase labelled according to the method of Nakane and Kawaoi (28).…”
Section: Methodsmentioning
confidence: 99%
“…The monoclonal antibodies MPW4UK and MPW5UK (22), both belonging to the IgG1 subclass and directed against u-PA, reacted with high as well as with low molecular weight u-PA. MPW5UK additionally interfered with plasminogen activation by u-PA. Radiolabeling of MPW5UK was performed as described for u-PA, resulting in a specific activity of 3.79 x 107 cpm//g.…”
mentioning
confidence: 99%
“…Preparation and Radiolabeling of u-PA. u-PA (double chain; Mr 54,000) was isolated from human urine by affinity chromatography on anti-u-PA monoclonal antibody (MPWSUK)-Sepharose followed by affinity chromatography on agmatine-Sepharose (22). SDS/PAGE followed by silver staining showed a single band in the unreduced samples, corresponding to Mr 54,000. u-PA (50 ,ug) was inactivated by incubation with 0.05 M DFP in 0.01 M potassium phosphate buffer (pH 7.4) for 2 hr at room temperature followed by excessive dialysis to remove free DFP; inactivated u-PA was found to be <0.5% as active as the native enzyme on plasminogen-rich fibrin/agarose plates (16).…”
mentioning
confidence: 99%
“…Details of the purification have been described elsewhere [16]. Although it was shown that the sc-uPA preparation used only exhibited a single silver-stainable band in the reduced and non-reduced sample, trace contamination of the sc-uPA preparation by the active high-Mr urokinase cannot, however, be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Sc-uPA and high-M, urokinase were isolated from human urine by affinity chromatography on monoclonal, antiurokinase IgG (MPW5UK)-Sepharose followed by affinity chromatography on agmatine-Sepharose to separate active bound from inactive unbound urokinase as described previously [16]. The two products were analyzed by SDS/polyacrylamide gel electrophoresis followed by silver staining and could be shown to consist of a single stainable protein band in the unreduced samples corresponding to an M , of 54000.…”
Section: Urokinasesmentioning
confidence: 99%